Wisma Sime Darby / Ahmad Dhiyauddin Ahmad Khair ... [et al.] - Ahmad Dhiyauddin, Ahmad Khair; Aisyah, Abu Bakar; Nor Syazana, Mohd Radzhi; Nur Iwani, Azman; Nurazam, Che Azelan (2019)
Integrated Final Project (IFP) is the most important report that should be prepared by the final year Student of AP 119 Program. The report of the final project require the group member to study and analyze the maintenance organization and management at their selected case study. The group shall then relate the collected data with their knowledge in how to build a well maintenance organization. At the end of this study, the students shall be able to identify the strength and weakness of the organization that emphasis to the property maintenance management. The objectives of the Integrated Final Project (IFP) are generally to deliver the comprehensive understanding on the importance of the property maintenance management. Besides, it also require the student to learn and analyze through the collected data of the multi-disciplinary approach in maintenance. In addition, the Integrated Final Project also require the students to be able to prepare a scientific technical report of the maintenance at their selected case study. Lastly, it also require the students to be able to communicate, work in team, cooperate and confidently present the report to the panel. For our group, the selected case study for the Integrated Final Project is Wisma Sime Darby which are located at Jalan Raja Laut, Kuala Lumpur. The method that has been implement by our group to gain the building information are generally through 3 basic phase. The first phase is by select the case study, then provide the Official Letter from UiTM to prove the student identification and also the cover letter from the student which to inform the intention and make the proper appointment with building owner through phone call and email. When we has gain the approval, the second phase is by doing the site visit, gather all the needed data and information and make the data and information analysis. The last phase is by preparing and completing the report by following the guidance provided. At the third phase, our group will have to go through the critique session with the subject supervisor, who responsible to supervise the report to ensure that we are on the right track and with the right format while accomplishing the report. The Integrated Final Project report is then will be submitted to the Program Coordinator for final submission and the student will do the presentation of their report in front of the panel.